2021
DOI: 10.1177/1077546320982136
|View full text |Cite
|
Sign up to set email alerts
|

Control of sound transmission into a hybrid double-wall sandwich cylindrical shell

Abstract: A 3D analytical model is formulated for diffuse sound field transmission control through a smart hybrid double concentric sandwich circular cylindrical shell structure in presence of external and internal air gap mean flows. The multi-input multi-output sliding mode control is applied to enhance the sound transmission loss characteristics via direct control action of a uniform force piezoelectric actuator layer along with semi-active variation of the stiffness/damping characteristics of the electrorheological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Fu et al [59] indicated the effects of gradient index, porosity volume fraction, and porosity distribution type on the variations of STL of a FG porous cylindrical shell under nonlinear thermal loading. Hasheminejad and Jamalpoor [60] improved the diffuse STL across a smart hybrid double concentric sandwich circular cylindrical shell structure under internal and external air gap mean flows using multi-input multi-output (MIMO) sliding mode control (SMC). According to the hyperbolic tangent shear deformation assumption, Li et al [61] calculated the natural frequencies and STL of FG honeycomb sandwich plates.…”
Section: Introductionmentioning
confidence: 99%
“…Fu et al [59] indicated the effects of gradient index, porosity volume fraction, and porosity distribution type on the variations of STL of a FG porous cylindrical shell under nonlinear thermal loading. Hasheminejad and Jamalpoor [60] improved the diffuse STL across a smart hybrid double concentric sandwich circular cylindrical shell structure under internal and external air gap mean flows using multi-input multi-output (MIMO) sliding mode control (SMC). According to the hyperbolic tangent shear deformation assumption, Li et al [61] calculated the natural frequencies and STL of FG honeycomb sandwich plates.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, structural vibration and noise related problems for such structures have drawn more attention due to the acoustic environment exposed to these structures. Several analytical and experimental studies were conducted to investigate the sound transmission characteristics through flat panels (Davy, 2009; Oyelade, 2020; Putra and Thompson, 2010; Zhou and Crocker, 2010), and cylindrical shells (Darvish Gohari et al, 2020; Hasheminejad and Jamalpoor, 2021; Lee and Kim, 2002, 2003; Talebitooti et al, 2018; Zhang, 2020).…”
Section: Introductionmentioning
confidence: 99%